Precision measurement of the mass and lifetime of the [Xi]−b baryon - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2014)
We report on measurements of the mass and lifetime of the Ξ−b baryon using about 1800 Ξ−b decays reconstructed in a proton-proton collision data set corresponding to an integrated luminosity of 3.0 fb−1 collected by the LHCb experiment. The decays are reconstructed in the Ξ−b→Ξ0cπ−, Ξ0c→pK−K−π+ channel and the mass and lifetime are measured using the Λ0b→Λ+cπ− mode as a reference. We measure M(Ξ−b)−M(Λ0b)=178.36±0.46±0.16 MeV/c2, (τΞ−b/τΛ0b)=1.089±0.026±0.011, where the uncertainties are statistical and systematic, respectively. These results lead to a factor of 2 better precision on the Ξ−b mass and lifetime compared to previous best measurements, and are consistent with theoretical expectations.
*LHCb Collaboration: R. Aaij, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und 673 weitere Personen]
Im Titel ist Xi als griechischer Buchstabe dargestellt
Im Titel ist das Zeichen - hochgestellt und der Buchstabe b tiefgestellt
Gesehen am 01.10.2020